f ( x ) = x x 2 − 3 x + 2
Which of the answers is closest to (or equal to) the value of f ′ ( 3 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Spot on! Another method I like to use in order to arrive at the value of f ′ ( x ) is the following:
f ( x ) = x x 2 − 3 x + 2 = e ln ( x x 2 − 3 x + 2 ) = e ( x 2 − 3 x + 2 ) ln ( x )
We can then find f ′ ( x ) using the chain rule.
f ( x ) = e ( x 2 − 3 x + 2 ) ln x
f ′ ( x ) = [(2 x - 3) ln x + ( x 2 − 3 x + 2 ) x 1 ] e ( x 2 − 3 x + 2 ) ln x
f ′ ( 3 ) = [3 ln 3 + 3 2 ] e 2 ln 3 = 27 ln 3 + 6 = 35.66253179403896166767162139690+
Answer: 3 6
∂ x ∂ x x 2 − 3 x + 2 ⇒ x x 2 − 3 x + 2 ( x x 2 − 3 x + 2 + ( 2 x − 3 ) lo g ( x ) ) .
Evaluated at x → 3 gives 9 ( 3 2 + 3 lo g ( 3 ) ) ≈ 3 5 . 6 6 2 5 3 1 7 9 4 0 3 9 .
Problem Loading...
Note Loading...
Set Loading...
The useful trick here is to take logs: f ( x ) = x x 2 − 3 x + 2 ⟹ ln ( f ( x ) ) = ( x 2 − 3 x + 2 ) ln ( x ) Taking the derivative we get: f ( x ) f ′ ( x ) = ( 2 x − 3 ) ln ( x ) + x x 2 − 3 x + 2 ⇒ f ′ ( x ) = f ( x ) ( ( 2 x − 3 ) ln ( x ) + x x 2 − 3 x + 2 )
Using the fact that f ( 3 ) = 9 we can deduce f ′ ( 3 ) = 9 ( 3 ln ( 3 ) + 3 2 ) = 2 7 ln ( 3 ) + 6 ≈ 3 6